2000
DOI: 10.1063/1.372851
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties and crystal structure of HoNiAl and UNiAl hydrides

Abstract: The effect of hydrogenation on the magnetic properties and crystal structure of 4f and 5f intermetallics was studied on HoNiAlH2.0, UNiAlH2.3 and UNiAlD2.1. The incorporation of hydrogen into HoNiAl leads to a decrease of the magnetic ordering temperature from 13 to 6 K, while it increases from 19 K to values in the range 90–100 K in the UNiAl–H system. The crystal lattices of all compounds are anisotropically expanded. Moreover, the crystal symmetry is lowered to orthorhombic in HoNiAlH2.0, but remains hexago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 11 publications
1
22
1
Order By: Relevance
“…Hydrogen insertion in HoNiAl is found to change its crystal structure from hexagonal to orthorhombic [489]. Hydrogenated HoNiAl shows very different properties compared to those of the parent compound.…”
Section: Hydrogenation Of Rtx Compoundsmentioning
confidence: 99%
“…Hydrogen insertion in HoNiAl is found to change its crystal structure from hexagonal to orthorhombic [489]. Hydrogenated HoNiAl shows very different properties compared to those of the parent compound.…”
Section: Hydrogenation Of Rtx Compoundsmentioning
confidence: 99%
“…Hydrogen absorption can take place at room temperature under H 2 (D 2 ) pressure of about 1 bar [2][3][4][5][6]. Previous studies of RENiAl have shown that both magnetic and structural properties are modified by hydrogenation [4,[7][8][9]. In most cases, the maximum hydrogen (deuterium) uptake reaches 1.0-1.4 atoms per formula unit and leads to an orthorhombic distortion of the original hexagonal structure (space group Amm2; a ∼ c hex ; b ∼ a hex √ 3; c ∼ a hex ) accompanied by a relative increase of cell volume, V/V ≤ 7% (RE = Y, Gd, Tb, Dy, Ho and Er) [4].…”
Section: Introductionmentioning
confidence: 99%
“…It may be noted that isostructural UNiAl forms hydride/deuteride with y w 2.2, indicating that the type of interstitial sites [20] and Bordallo et al [21] who reported the occupancy of 3Al þ 2Ni, which seems quite unlikely. Comparing with other UTX compounds, in URuSnD 0.6 [10] the D atoms occupy the trigonal bipyramidal sites formed by 3U þ 2Ru, similar to one of the sites in UNiAlD 2.2 .…”
Section: 2mentioning
confidence: 95%